PENGARUH KOMBINASI TERAPI RELAKSASI BENSON DAN TERAPI MUSIK TERHADAP TINGKAT NYERI PASIEN KANKER PAYUDARA POST OPERASI MODIFIED RADICAL MASTECTOMY - Suryandari, Dewi; Fatimah, Rizki Nur; Kurniawan, Sahuri Teguh (Jurnal Keperawatan dan Kesehatan, 2025)
Pain is sometimes still felt by patients even though they have received analgesic therapy, so non-pharmacological therapy is needed that can reduce the pain felt by postoperative patients. Benson relaxation with a combination of music therapy is a relaxation technique that can be used to relieve pain. The purpose of this study was to determine the effect of a combination of benson relaxation therapy and music therapy on pain levels. This study used a type of pre-experimental research with a one group pre test-post test design. The research was conducted in the inpatient room of Dr. Moewardi Surakarta Hospital in February 2025. The sample used was 38 patients with purposive sampling technique. Data collection tools using numeric rating scale pain assessment questionnaire sheet and SOP combination of Benson relaxation and Mozart music therapy. The data analysis used was Wilcoxon analysis. The results showed that the characteristics of respondents based on the age of the respondents were mostly aged 25-44 years as many as 23 people (60,5%), the most respondent education was junior high school education as many as 19 people (50%), the most respondent disease history was having a history of disease as many as 28 people (73.7%). The average pain scale before the intervention was 5.45, while after the intervention was 4.26. The conclusion is that there is an effect of giving benson relaxation therapy combined with music therapy on the pain level of Modified Radical Mastectomy (MRM) surgery patients at Dr. Moewardi Hospital (p value 0.000).